UNESCO's Contribution to the International Protection of Tradition Cultural Expressions and Knowledge - Asiia Sh. Gazizova, Adel I. Abdullin, (Opción, 2019)
This paper is devoted to the analysis of the approach of UNESCO to the protection of traditional cultural expressions and knowledge. As a method, the authors consider the chronological sequence of the inclusion of this issue in the agenda at international conferences. As a result, intangible cultural heritage propagated is constantly recreated by communities and groups depending on their environment, their interaction with nature and their history and forms with them a sense of identity and continuity. In conclusion, UNESCO follows a comprehensive approach, unlike the World Intellectual Property Organization, which focuses on preventing and warning on their illegal use.